2015
DOI: 10.1080/09537287.2015.1027318
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of product complexity on new product development and supply chain management integration

Abstract: The purpose of this study is to investigate whether product complexity moderates the impact of integration programs in both new product development (NPD) and supply chain (SC) management on operational performance. Results are based on statistical analyses of data collected from an international sample of manufacturing firms through the fifth edition of the International Manufacturing Strategy Survey (IMSS 5). The main findings are that NPD and SC integration do have an impact on performance, while product com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…Furthermore, the speed of the ramp-up strongly affects the time-to-volume of a product and subsequently the financial success of the new product and the company (Haller, Peikert & Thoma, 2003). All those issues can be managed by integrating NPD and SC processes by SCCC activities (Lakemond, Echtelt & Wynstra, 2001;Ball, Roberts, Natalicchio & Scorzafave, 2011;Elstner & Krause, 2014;Surbier, Alpan & Blanco, 2014;Caniato & Größler, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the speed of the ramp-up strongly affects the time-to-volume of a product and subsequently the financial success of the new product and the company (Haller, Peikert & Thoma, 2003). All those issues can be managed by integrating NPD and SC processes by SCCC activities (Lakemond, Echtelt & Wynstra, 2001;Ball, Roberts, Natalicchio & Scorzafave, 2011;Elstner & Krause, 2014;Surbier, Alpan & Blanco, 2014;Caniato & Größler, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lately, the attention on the issues related to the linkage and interrelationship between NPD and supply-chain (SC) has increased in research and practice (Pero et al, 2010;Caniato & Größler, 2015). SC and NPD processes are highly connected because the supply-chains supply, produce and distribute the products defined during the product development activities (Pero et al, 2010).…”
Section: Supply-chain Capability Creation Processmentioning
confidence: 99%
“…It is also remarkable that there is no more research related to NPD and rollover decision. NPD has a decisive impact on key management directions, such as production, marketing, and supply chain management (Gunasekaran 1998, Pero et al 2010, Gmelin and Seuring 2014, Caniato and Gröβler, 2015. Especially the latter, supply chain management, should be of greater interest.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…However, [32] in their research found that this complexity also brings in new growth opportunities (58% of responders), and possible competitive advantage (59.4% of responders). [33] researched product complexity in new product development (NPD). Although, as [32] show, complexity of the product should increase new product potential developments, [33] found no impact of complexity on new product performance measures.…”
Section: Complexity Of the Productmentioning
confidence: 99%